Pain and athletes. Contact sport participation and performance in pain - Sheffield, D.; Thornton, C.; Jones, M. V. (Psychology of Sport and Exercise, 2020)
Objectives: This study examined the effect of cold pressor pain on performance in high-contact athletes, low-contact athletes and non-athletes.